N-(Fluoren-9-ylmethoxycarbonyl)-l-leucine - Yamada, Kazuhiko (International Union of Crystallography, 2008)
The title compound [systematic name: fluoren-9-yl N-(1-carboxy-3-methylbutyl)carbamate], C(21)H(23)NO(4), exhibits torsion angles that vary from the typical values found in other Fmoc-protected amino acids, viz. the orientations of the fluorene and carboxyl groups [C—O—C—C = 93.8 (2) and N—C—C=O = −23.6 (2)°]. The crystal structure exhibits two intermolecular hydrogen bonds (O—H⋯O and N—H⋯O) that link the molecules into two-dimensional sheets parallel to the ab plane.